Impact of Third-Party Funds and Capital Adequacy Ratio on Profit Sharing Financing - Peny Cahaya Azwari; Febriansyah Febriansyah; Sri Delasmi Jayanti (International Business and Accounting Research Journal, 2022)
Financing is defined as funding provided by a party to another party to support planned investments, either by themselves or by institutions. The more amount of Third-Party Funds (DPK) and Capital Adequacy Ratio (CAR), the more amount of financing issued by the bank. However, in the 2016-2020, when Shariah Business Units in Indonesia increase in the amount of Third-Party Funds (DPK) and the Capital Adequacy Ratio (CAR) but this was inversely proportional to the declining amount of profit-sharing financing. This study aims to determine how the influence of Third-Party Funds (DPK) and Capital Adequacy Ratio (CAR) on Profit Sharing Financing in Sharia Business Units. Using quantitative methods and the type of data used was secondary data, researchers use the Annual Report. By eleven sharia business units as samples of this study, the results show that TPF variable has a negative and significant effect on profit sharing financing and the CAR variable has no and no significant effect on profit sharing financing. Meanwhile, based on the f test, TPF and CAR variables simultaneously have a positive and significant effect on profit sharing financing in sharia business unit.